AN ANALYSIS OF ELASTICITY OF DEMAND FOR LOCAL RICE IN NASARAWA LOCAL GOVERNMENT AREA OF NASARAWA STATE, NIGERIA - Abdullahi, Abubakar Okuwa; Goyilla, Abigail Elisha (African Journal of Social and Behavioural Sciences, 2024)
Rice consumption outweighs production in Nigeria, resulting in high demand, high prices, greater incentives for local rice production and the importation of foreign rice. Against this background, this study attempts to empirically analyse the elasticity of demand for local rice in the Nasarawa Local Government Area of Nasarawa State, Nigeria. The survey method was used for the study population of 839 personnel in the Nasarawa Local Government. Purposive and stratified random sampling techniques were used to select samples for the study. Cross-sectional data were collected from January to March 2024 using structured questionnaires and analysed using SPSS 15. The ordinary least squares (OLS) multiple regression technique was used for the model and parameter estimation. The study revealed that; the coefficient of the price of local rice (plr) is negative, less than 1 in absolute terms but significant at the 1% level, the coefficient of the income level of consumers (ilc) is positive but less than 1 and statistically significant at the 5% level, and the coefficient of the price of foreign rice (pfr) is positive but less than 1 and significant at the 10% level. Therefore, the study concluded that the price of local rice (plr), the income level of consumers (ilc) and the price of foreign rice (pfr) are significant determinants of the elasticity of demand for local rice (DLR) in the Nasarawa Local Government Area of Nasarawa State. The study recommends that the government should control prices, increase salaries and wages and encourage the importation of foreign rice to reduce the price, income and cross effects on the quantity demand of local rice.